\(5\sqrt{2x^2-3x+1}=\frac{8x^2-9x+3}{x}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(P=\Sigma_{cyc}\sqrt{\frac{a}{a+1}}=\Sigma_{cyc}2\sqrt{\frac{1}{4}\left(1-\frac{1}{a+1}\right)}\)
\(\le\Sigma_{cyc}\left[\frac{1}{4}+\left(1-\frac{1}{a+1}\right)\right]=\frac{15}{4}-\left(\frac{1}{a+1}+\frac{1}{b+1}+\frac{1}{c+1}\right)\)
\(\le\frac{15}{4}-\frac{9}{a+b+c+3}=\frac{3}{2}\)
Đẳng thức xảy ra khi \(a=b=c=\frac{1}{3}\)
Cách khác:
\(P=\Sigma_{cyc}\sqrt{\frac{a}{a+1}}=\Sigma_{cyc}\sqrt{a.\frac{1}{\left(a+b\right)+\left(a+c\right)}}\)
\(\le\Sigma_{cyc}\sqrt{\frac{1}{4}a\left(\frac{1}{a+b}+\frac{1}{a+c}\right)}=\frac{1}{2}\Sigma_{cyc}\sqrt{1\left(\frac{a}{a+b}+\frac{a}{a+c}\right)}\)
\(\le\frac{1}{4}.\Sigma_{cyc}\left(1+\frac{a}{a+b}+\frac{a}{a+c}\right)=\frac{3}{2}\)
Đẳng thức xảy ra khi a = b = c
ĐK: \(\frac{3-\sqrt{5}}{2}\le x\le\frac{3+\sqrt{5}}{2}\)( do VT<0)
\(x^2-3x+1=-\frac{\sqrt{3}}{3}\sqrt{x^4+x^2+1}\)
\(\Leftrightarrow x^2-2x+1=x-\frac{\sqrt{3}}{3}\sqrt{x^4+x^2+1}\)
\(\Leftrightarrow\left(x-1\right)^2=\frac{x^2-\frac{1}{3}\left(x^4+x^2+1\right)}{x+\frac{\sqrt{3}}{3}\sqrt{x^4+x^2+1}}\)
\(\Leftrightarrow\left(x-1\right)^2=\frac{3x^2-x^4-x^2-1}{3x+\sqrt{3}.\sqrt{x^4+x^2+1}}\)
\(\Leftrightarrow\left(x-1\right)^2=\frac{-\left(x^2-1\right)^2}{3x+\sqrt{3}.\sqrt{x^4+x^2+1}}\)
\(\Leftrightarrow\left(x-1\right)^2\left[1+\frac{1}{3x+\sqrt{3.\left(x^4+x^2+1\right)}}\right]=0\)
\(\Leftrightarrow\left(x-1\right)^2=0\) ( \(1+\frac{1}{3x+\sqrt{3.\left(x^4+x^2+1\right)}}>0\left(ĐK\right)\)
\(\Leftrightarrow x=1\)
Kết Luận:...